EMBOLIZATION UTERINE BLEEDING OF EMERGENCY IN MASS - Quevedo, Ernesto (2015)
OBJETIVE:To evaluate efficacy and safety of emergency selective uterine artery embolization in the management of intractable hemorrhage when the patient is haemodinamically unstable. SETTING: Interventionist Radiology Service, Guillermo Almenara Irigoyen National Hospital, Lima, MATERIAL AND METHODS: Six patients with life?threatening hemorrhage underwent uterine hemostatic uterine embolization. The mean hemoglobin level before the procedure was 5,2 g/dL. RESULTS: Immediate reduction of external bleeding was observed in all cases. No major complications related to embolization was found. Two patients underwent hysterectomy in stable conditions. CONCLUSIONS: Emergency embolization is a safe and effective procedure to control severe hemorrhage. The procedure obviates high risk emergency surgery.